PENILAIAN KINERJA BANGUNAN GEDUNG HIJAU PADA GEDUNG FAKULTAS KIP UNIVERSITAS SAMUDRA - Alnanda Hafiez Lagalgarin; Meilandy Purwandito; Nova Purnama Lisa (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: Climate change occurs due to increasing concentrations of carbon dioxide gas causing the greenhouse gas effect. The building construction sector has increased and is known to contribute more than 34 percent of carbon emissions by 2022. So that one of the steps in reducing carbon emissions in the construction sector is by implementing green buildings. Green buildings are buildings that meet the criteria for saving energy, water, and other resources. In assessing the performance of green buildings, there are three criteria rating levels ie: pratama, madya, and utama. This study uses a qualitative descriptive method with identifying observation elements, simulation as well as investigations that will be applied in the BGH assessment. This study aims to analyze the building of the Faculty of KIP Universitas Samudra following the reference of the Ministerial Circular Letter No.01/SE/M/2022 concerning Technical Guidelines for Performance Assessment of Green Buildings. Based on the results of the performance assessment of the Samudra University Faculty of KIP building were included in the